Eksistensi Taubat dan Syubhat dalam Pelaksanaan Hudud (Studi terhadap Pandangan Imam Abu Hanifah) - Atika Atika (Pusat Penelitian dan Penerbitan Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Islam Negeri Raden Fatah Palembang, 2015)
This research paper discusses about Imam Abu Hanifah’s perspective on the existence of taubat and syubhat in hudud implementation. This study summarizes that the meaning of taubat according to Imam Abu Hanafah is very different from the other Muslim experts who can abort repentance only in terms of hadd hirabah (robbery), but cannot be applied for the other cases. Moreover, his perspective on syubhat is very broad compared to the other experts if it is related to hudud. Based on his, it cannot be imposed on hudud but to takzir. Hudud can be done if it does not have syubhat elements.